PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PEMBERIAN PELAYANAN PUBLIK DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KUTAI BARAT - . Mulyadi (Jurnal Paradigma (JP), 2017)
The purpose of this study to describe and analyze of Implementation of the principle of good governance the public service in the Departement of Transportation, Communication and Informatics at West Kutai Regency. The method used is descriptive qualitative. Analysis is an interactive model.The results showed Implementation of the principleof good gover-nancene the public service in departemnt of transportation communication and informatics West Kutai is generally quite effctive. However apllicative before by various abstacles so that not all the principles of good governance effective, that not all the principles of new gets implemented effectively.Keywords: implementation, good governance, public service